(untitled) (Scientific journal of the Fergana State University, 2023)
In our research work, a method is presented for determining the quantitative composition and content in wt.% Of oil or oil products in engine oils. An analytical method for the quantitative analysis of oil in engine oil has been carried out. This analytical method is used to determine the content of petroleum oils in an engine oil classified in HS subheading 2710 or 3403.